DNA–melamine hybrid molecules: from self-assembly to nanostructures - Kumari, Rina; Banerjee, Shib Shankar; Bhowmick, Anil K.; Das, Prolay (Beilstein Journal of Nanotechnology, 2015)
Single-stranded DNA–melamine hybrid molecular building blocks were synthesized using a phosphoramidation cross-coupling reaction with a zero linker approach. The self-assembly of the DNA–organic hybrid molecules was achieved by DNA hybridization. Following self-assembly, two distinct types of nanostructures in the form of linear chains and network arrays were observed. The morphology of the self-assembled nanostructures was found to depend on the number of DNA strands that were attached to a single melamine molecule.
Keywords: DNA–organic hybrid; melamine; nanostructures; phosphoramidation; self-assembly